Influence of annealing time on the physical properties of reactively sputtered CuO thin film - Akgul, Unal; Yildiz, Koksal; Atici, Yusuf (Springer, 2017)
Polycrystalline CuO thin film was deposited by reactive RF magnetron sputtering technique. The samples obtained from CuO film were annealed in air for different times. The structural, compositional and optical properties of unannealed and annealed samples were characterized. The SEM studies showed that the samples have a homogeneous surface morphology. All of the samples exhibited strong diffraction peak and optical transmittance above 70%. As the annealing time was increased, the grain size increased and the optical band gap decreased.
Keywords: Photocatalytic Performance; Transistors; Cuo/Zno